GEOCHEMICAL CHARACTERISTICS OF THE MAIN ORE COMPONENTS IN THE GOSHGARCHAY PORPHYRY-EPITHERMAL SYSTEM (LESSER CAUCASUS, AZERBAIJAN) - MANSUROV, Mamoy (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article deals with the determining characteristics of ore elements in the Goshgarchay porphyry-epithermal system. The genetic and geochemical characteristics of the main ore components were studied, and close positive and negative relationships between pairs of elements were determined by correlation analysis on the selected elements. According to the results of the cluster analysis, the geochemical associations that allow the localization of the development area of mineralization at different stages of formation of the porphyry-epithermal system were analyzed. The following series of stable elements, which are typical for hydrothermal deposits, are distinguished among the ore elements of the host and ore-bearing intrusive rocks: Cu, Mo, Pb, Zn, Ag, Ni, Co, Mn, Ti, Cr, V, Sr, etc. This group of elements is considered to be the indicator elements of the copper-porphyry deposit within the porphyry-epithermal system. It has been determined that correlations between elements in copper-porphyry mineralization are characterized by a wide range of element impurities. It includes both chalcophile (As, Sb, Cu, Bi, Cd, Ga, In, Ge, Au, Ag, Te) and siderophile (Co, Ni, Mo, Fe, Cr) elements. The range of values of vertical geochemical zonality on individual sections of the deposit allows to assess the level of the erosion truncation of occurrences in the porphyry-epithermal system.
Keywords: Goshgarchay; porphyry-epithermal; geochemical; main ore components; correlation relationship; genetic characteristics